How important are global factors for understanding the dynamics of international capital flows? - Markus Eller; Florian Huber; Helene Schuberth (University of Salzburg, Department of Social Sciences and Economics, 2018)
We propose a dynamic factor model with time-varying parameters and stochastic volatility to analyze the relationship between global factors and country-specific capital flow dynamics. Studying a global sample of 43 countries from 1994 until 2015, we show that global co-movement of macroeconomic, financial and capital flow variables can explain a major share of country-specific capital flow volatility and that the impact of these variables has become even more important since the 2008-2009 global financial crisis. Our results indicate that country-specific changes in capital flows are strongly affected by fluctuations in global financial cycles and - to some extent - by global real business cycles. There is some evidence that countries with higher foreign exchange reserves, flexible exchange rates, lower public indebtedness or more developed domestic stock markets may better shield themselves from the global financial cycle.
Keywords: C38; F32; F41; F42; F44; 330; Volatility of capital flows; dynamic factor model; stochastic volatility; global co-movement; global real business cycle; global financial cycle